Biomass Production of Gynura procumbens Adventitious Roots in Different Type of Liquid Culture - Yosephine Sri Wulan Manuhara; Dannis Yuda Kusuma; Rafika Lailiyatul Kurnia Sari; Alfinda Novi Kristanti (Biosaintifika: Journal of Biology & Biology Education, 2017)
Gynura procumbens has a potency to produce raw material for pharmaceutical industry. Liquid culture systems have significant effects on multiplication rates of organ, so the propagation technology to increase biomass of this plant or organ using the liquid culture system was necessary. This research was conducted to compare biomass production of adventitious roots of G. procumbens in different liquid culture (shake flask, temporary immersion bioreactor and balloon-type bubble bioreactor). Adventitious roots culture was maintained in Murashige and Skoog liquid medium supplemented with IBA (indole butyric acid) 5 mg/L and different concentrations of sucrose (10, 30, 50 g/L). Result showed that the highest biomass production (fresh weight) was in shake flask that was 3.9-fold higher than initial explant, while in temporary immersion system was 5.12-fold higher than initial explant, and in balloon- type bubble bioreactor was 13.1-fold higher than initial explant. The highest enhancement of adventitious roots was occurred at sucrose supplementation of 50 g/L. Based on this research we found that the best type of liquid culture to increase biomass of G. procumbens adventitious roots was balloon-type bubble bioreactor. Scaling-up of adventitious root culture are necessary to fulfill the need of raw material for pharmaceutical industry and ballon-type bubble bioreactor was the most suitable method to scale up the performance.